Integrated genomics and functional validation identifies malignant cell specific dependencies in triple negative breast cancer - Nirmesh Patel (Nature Portfolio, 2018)
Triple negative breast cancers harbor multiple copy number aberrations driving gene expression changes thought to underpin their malignant phenotypes. Here the authors integrate these features, finding and functionally validating 37 gene addictions among which they identify the mechanism of addiction to KIFC1, a potential selective drug target.